Factors associated with COVID-19 vaccination schedule completion among adults in high-social-vulnerability neighborhoods in two Brazilian state capitals: A cross-sectional study - Fernanda Martins Iunes; Thaís Aranha Rossi; Fabiane Soares; Thiago S Torres; Valdilea G. Veloso; Débora Castanheira; Nathalia Suzart; Felipe Fagundes Soares; Alexandro Gesner Gomes dos Santos; Diana Zeballos; Ines Dourado; Laio Magno (PLoS ONE, 2026)
This study aimed to examine the factors associated with Coronavirus disease 2019 (COVID-19) vaccination schedule completion among adults in socially vulnerable neighborhoods in two Brazilian state capitals. This cross-sectional study analyzed the data of individuals who attended primary healthcare (PHC) units in Salvador and Rio de Janeiro between July 2022 and May 2023. Data were collected using a structured sociobehavioral questionnaire. The outcome variable was COVID-19 vaccination schedule completion, defined as receiving ≥1 booster dose in the primary series (i.e., first and/or second dose or single-dose vaccine) plus one booster dose. The association between predictor variables and vaccination schedule completion was evaluated using multiple logistic regression. A total of 7,193 participants who reported having received ≥1 dose was included, 79.35% had completed the vaccination schedule. Participants aged >50 years (odds ratio [OR]=3.83; 95% confidence interval [CI]: 3.11–4.70), and cisgender women (OR=1.38; 95%CI: 1.20–1.57) and those with higher or graduate education (OR=2.44; 95%CI: 1.99–2.99), ≥ 2 comorbidities (OR=2.14; 95%CI: 1.56–2.92), mixed public and private healthcare use (OR=1.56; 95%CI: 1.30–1.89), a medical consultation in the last 12 months (OR=1.60; 95%CI: 1.38–1.85), and those who sought care at a primary health care unit in the last 12 months (OR=1.20; 95%CI: 1.03–1.41) had a higher odds of adherence to the scheduled vaccination than their respective counterparts. Conversely, individuals of Evangelical belief (OR=0.63; 95%CI: 0.56–0.72) and individuals residing in households with high occupancy density (OR=0.69; 95%CI: 0.57–0.82) showed lower vaccination completion than their respective counterparts. This study demonstrated that sociodemographic and healthcare-related factors play a pivotal role in supporting COVID-19 vaccination adherence, contributing to higher coverage rates and reducing inequalities in vaccine access. Active outreach to unvaccinated individuals and strengthening primary healthcare are essential for increasing vaccination coverage and mitigating inequalities in access to health services.